2018
DOI: 10.1161/circulationaha.117.029193
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Urinary Sodium and Potassium Excretion and Blood Pressure Among Adults in the United States

Abstract: These cross-sectional results show a strong dose-response association between urinary sodium excretion and blood pressure, and an inverse association between urinary potassium excretion and blood pressure, in a nationally representative sample of US adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
138
3
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(161 citation statements)
references
References 32 publications
13
138
3
7
Order By: Relevance
“…Similar to other studies, increasing BMI was associated with higher salt consumption . The association found in this study between systolic blood pressure and salt intake in the general population is consistent with other studies . Despite the widespread knowledge that salt consumption is a major nutritional factor associated with SBP level, we did not find statistically significant association between SBP among non‐hypertensive participants in a stratified analysis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to other studies, increasing BMI was associated with higher salt consumption . The association found in this study between systolic blood pressure and salt intake in the general population is consistent with other studies . Despite the widespread knowledge that salt consumption is a major nutritional factor associated with SBP level, we did not find statistically significant association between SBP among non‐hypertensive participants in a stratified analysis.…”
Section: Discussionsupporting
confidence: 90%
“…26 The association found in this study between systolic blood pressure and salt intake in the general population is consistent with other studies. [27][28][29] Despite the widespread knowledge that salt consumption is a major nutritional factor associated with SBP level, we did not find statistically significant association between SBP among non-hypertensive participants in a stratified analysis. This result should be interpreted cautiously, because the sample size was small and the design was cross-sectional.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The relationship between K + and blood pressure in the INTERSALT, PURE, and NHANES studies persisted after adjusting for confounding variables [6,41,42]. The DASH-trial was an intervention study and showed that with constant sodium intake, an increase in dietary K + reduced blood pressure [43].…”
Section: Discussionmentioning
confidence: 97%
“…The association of high sodium and low potassium intake with elevated blood pressure is supported by a large body of evidence that includes randomized clinical trials, 4,5 as well as observational cohort studies. 6,7 The Trials of Hypertension Prevention (TOPH), conducted in 1987-1990 and 1990-1995, respectively, showed that reducing dietary sodium in individuals with prehypertension decreased the risk of cardiovascular events and overall mortality up to 20 years after the original trial. [8][9][10] For CVD, two previous meta-analyses of prospective cohort studies detected significant positive relationships between sodium intake and stroke, as well as CVD outcomes.…”
Section: Introductionmentioning
confidence: 99%